MYO7A is required for the functional integrity of the mechanoelectrical transduction complex in hair cells of the adult cochlea - Anna Underhill; Samuel Webb; Fiorella C. Grandi; Jing-Yi Jeng; Jacques B. de Monvel; Baptiste Plion; Adam J. Carlton; Ana E. Amariutei; Niovi Voulgari; Francesca De Faveri; Federico Ceriani; Mirna Mustapha; et al. (Proceedings of the National Academy of Sciences, 2025)
Myosin-VIIA (MYO7A) is an unconventional myosin responsible for syndromic (Usher 1B) or nonsyndromic forms of deafness in humans when mutated. In the cochlea, MYO7A is expressed in hair cells, where it is believed to act as the motor protein tensioning the mechanoelectrical transducer (MET) channels, thus setting their resting open probability ( P o ). However, direct evidence for this unique role for an unconventional myosin in mature hair cells is lacking. Here, we show that MYO7A has a distinct role in hair cells, being crucial for the structural integrity of hair bundles. Postnatal deletion of Myo7a leads to 87 to 96% reduction in MYO7A from hair cells by postnatal day 20 (P20), without affecting hearing function. During the following week, mice showed progressive decline in both hearing function and MET current amplitude in hair cells without affecting the resting P o and calcium sensitivity of the MET channel. Hair-bundle stiffness was normal at P20 but halved at P30, despite it having a normal staircase morphology and tip links. The reduction of MYO7A in the stereocilia (>87%) increased their vulnerability to sound-induced damage, with significantly more hearing loss and hair bundle deterioration than in control mice. RNA-sequencing identified a downregulation of several stereociliary genes in the Myo7a -deficient cochlea, indicating the presence of indirect compensatory mechanisms. This study reveals that mature hair cells seem to use a MYO7A-independent mechanism to maintain the resting P o of the MET channels. Instead, MYO7A is essential for maintaining the structural and functional integrity of the hair bundles.